A rare case of pulmonary lymphangiomatosis from the tribal zone of central India - Khunte, Prakash; Beck, Pradeep; Khunte, Sanjeev; Prakash, Deepti (International Journal of Research in Medical Sciences, 2017)
Lymphangiomatosis, a rare disease, occurs in individuals of any age, regardless of gender, but is predominantly seen in younger individuals. It often presents with pulmonary involvement, although, the bones, spleen and liver can also be affected. Histologically, pulmonary involvement includes proliferation, complex anastomoses and secondary dilatation of the lymphatic vessels. Clinically presentation is often variable but pulmonary involvement is affected more common than other involvements. Diagnosis is made histologically but radiologically can suggest diseases. Treatment is only supportive and symptomatic.